The effect of GLP-1 receptor agonist lixisenatide on experimental diabetic retinopathy - Özer, Kübra; Kolibabka, Matthias; Gassenhuber, Johann; Dietrich, Nadine; Fleming, Thomas; Schlotterer, Andrea; Morcos, Michael; Wohlfart, Paulus; Hammes, Hans-Peter (Acta diabetologica, 2023)
Glucagon-like peptide-1 receptor agonists are effective treatments for type 2 diabetes, effectively lowering glucose without weight gain and with low risk for hypoglycemia. However, their influence on the retinal neurovascular unit remains unclear. In this study, we analyzed the effects of the GLP-1 RA lixisenatide on diabetic retinopathy.
Online veröfffentlicht: 9. Juli 2023
Gesehen am 02.09.2024